Loss of REDD1 prevents chemotherapy‐induced muscle atrophy and weakness in mice. Issue 6 (19th October 2021) - Hain, Brian A.; Xu, Haifang; Waning, David L.
Abstract: Background: Chemotherapy is an essential treatment to combat solid tumours and mitigate metastasis. Chemotherapy causes side effects including muscle wasting and weakness. Regulated in Development and DNA Damage Response 1 (REDD1) is a stress‐response protein that represses the mechanistic target of rapamycin (mTOR) in complex 1 (mTORC1), and its expression is increased in models of muscle wasting. The aim of this study was to determine if deletion of REDD1 is sufficient to attenuate chemotherapy‐induced muscle wasting and weakness in mice. Methods: C2C12 myotubes were treated with carboplatin, and changes in myotube diameter were measured. Protein synthesis was measured by puromycin incorporation, and REDD1 mRNA and protein expression were analysed in myotubes treated with carboplatin. Markers of mTORC1 signalling were measured by western blot. REDD1 global knockout mice and wild‐type mice were treated with a single dose of carboplatin and euthanized 7 days later. Body weight, hindlimb muscle weights, forelimb grip strength, and extensor digitorum longus whole muscle contractility were measured in all groups. Thirty minutes prior to euthanasia, mice were injected with puromycin to measure puromycin incorporation in skeletal muscle. Results: C2C12 myotube diameter was decreased at 24 ( P = 0.0002) and 48 h ( P < 0.0001) after carboplatin treatment. Puromycin incorporation was decreased in myotubes treated with carboplatin for 24 ( P = 0.0068) and 48 h ( P = 0.0008). REDD1 mRNA and protein expression were increased with carboplatin treatment ( P = 0.0267 and P = 0.0015, respectively), and this was accompanied by decreased phosphorylation of Akt T 308 ( P < 0.0001) and S 473 ( P = 0.0006), p70S6K T 389 ( P = 0.0002), and 4E‐binding protein 1 S 65 ( P = 0.0341), all markers of mTORC1 activity. REDD1 mRNA expression was increased in muscles from mice treated with carboplatin ( P = 0.0295). Loss of REDD1 reduced carboplatin‐induced body weight loss ( P = 0.0013) and prevented muscle atrophy in mice. REDD1 deletion prevented carboplatin‐induced decrease of protein synthesis ( P = 0.7626) and prevented muscle weakness. Conclusions: Carboplatin caused loss of body weight, muscle atrophy, muscle weakness, and inhibition of protein synthesis. Loss of REDD1 attenuates muscle atrophy and weakness in mice treated with carboplatin. Our study illustrates the importance of REDD1 in the regulation of muscle mass with chemotherapy treatment and may be an attractive therapeutic target to combat cachexia.